The reluctant assassin [compact disc, unabridged] - Colfer, Eoin (Colfer, Eoin. W.A.R.P., 2013)
In Victorian London, Albert Garrick, an assassin-for-hire, and his reluctant young apprentice, Riley, are transported via wormhole to modern London, where Riley teams up with a young FBI agent to stop Garrick from returning to his own time and using his newly acquired scientific knowledge and power to change the world forever.